Bitter taste disrupts spatial discrimination of piperine-evoked burning sensations: A pilot study - Liu, David T.; Besser, Gerold; Bayer, Karina; Prem, Bernhard; Mueller, Christian A.; Renner, Bertold (Biology, 2021)
This study aimed to investigate the perceptual similarity between piperine-induced burning sensations and bitter taste using piperine-impregnated taste strips (PTS). This pilot study included 42 healthy participants. PTS of six ascending concentrations (1 mg, 5 mg, 10 mg, 15 mg, 20 mg, and 25 mg piperine/dL 96% ethanol) were presented at the anterior tongue, and participants rated perceived intensity and duration. Then, participants performed a spatial discrimination task in which they had to report which of the two strips presented to the anterior tongue contained an irritating stimulus when one strip was always a PTS while the other strip was impregnated with either a single taste quality (sweet or bitter) or a blank strip. Repeated measures one-way ANOVA revealed that burning sensations of higher concentrated PTS were perceived more intense and more prolonged compared to lower concentrated PTS. McNemar’s test showed that PTS were identified correctly significantly less often when presented with bitter strips compared to when presented with blank (p = 0.002) or sweet strips (p = 0.017). Our results showed that bitter taste disrupts the spatial discrimination of piperine-evoked burning sensations. PTS might serve as a basis for further studies on disease-specific patterns in chemosensory disorders.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Chemesthesis; Chemical senses; Gustation; Piperine; Tongue; Trigeminal